The corn grows ripe - Rhoads, Dorothy; Charlot, Jean, 1898-1979 (New York : Puffin, 1993)
Tigre, a twelve-year-old Mayan boy living in a modern-day village in Yucatán, must learn to be a man when his father is injured.
"First published in the United States of America by the Viking Press, 1956"--T.p. verso.
5.0
3-6
Newbery Medal/Honor, 1957
3-6
Newbery Medal/Honor
Keywords: Mayas -- Juvenile fiction; Mayas -- Fiction; Indians of Mexico -- Fiction; Mayas -- Fiction; Native Americans -- Mexico -- Fiction; Mexico -- Fiction; Mexico -- Fiction